Penerapan Sistem Pembukuan dan Administrasi yang Efisien pada UMKM Iluh Craft untuk Mendukung Kesiapan Ekspansi Internasional (Lembaga Pengembangan Kinerja Dosen, 2026)
Micro, small, and medium enterprises (MSMEs) are required to establish well-organized bookkeeping and administrative systems to enhance competitiveness and readiness for international expansion. However, Iluh Craft MSME continues to face challenges related to unstructured financial record-keeping and traditional administrative practices, which hinder effective financial monitoring and the preparation of business documentation. This community service activity aims to implement an efficient bookkeeping and administrative system to improve recording accuracy, operational efficiency, and the readiness of Iluh Craft MSME to expand into international markets. The implementation employed a descriptive participatory approach involving interviews, observations, and documentation, followed by system design, phased implementation, mentoring, and joint evaluation with the partner. The results demonstrate a significant improvement in the accuracy of financial records, a reduction in transaction recording errors to below 5%, administrative time efficiency gains of approximately 25–30%, and improved document organization with faster data retrieval. In addition, more than 90% of staff members were able to operate the system independently. Overall, the implementation of an efficient bookkeeping and administrative system proved effective in supporting more professional business management and enhancing the readiness of Iluh Craft MSME for international market expansion.